Радиолокационные методы обнаружения беспилотных летательных аппаратов - Пархомов, А. О. (ХНУРЕ, 2021)
Small, unmanned aerial vehicles (UAVs), often called drones, are enabling unprecedented applications but, at the same time, new threats are arising linked to their possible misuse. The main challenges related to the problem of drone identification are discussed, which include detection, possible verification, and classification. An overview of the most relevant technologies is provided. More specifically, the main focus is on the frequency modulated continuous wave (FMCW) radar sensor, which is a key technology also due to its low cost and capability to work at relatively long distances, as well as strong robustness to illumination and weather conditions.
Keywords: БПЛА; мультикоптерные дроны